2020
DOI: 10.3389/feduc.2020.00094
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Stress Among Undergraduate Learners: The Importance of Emotional Intelligence, Resilience, and Emotion Regulation

Abstract: In the current investigation, we examined the association among emotional intelligence, emotional regulation tendencies, resilience, and perceived stress within a sample of undergraduate students. Participants (N = 277, 71% Female, 55% White) completed the Brief Emotional Intelligence Scale, Emotion Regulation Questionnaire, Brief Resilience Scale, and Perceived Stress Scale. Using path analysis techniques, we demonstrated that resilience was a negative predictor of perceived stress. Additionally, our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 56 publications
3
20
0
Order By: Relevance
“…Studies linking EI and AP often cite AR as a contextual resource (Thomas & Zolkoski, 2020;Suleman et al, 2019), which suggests that AR relates with both EI and AP (Slåtten et al, 2021). Concerning the AR-AP link, Bittmann (2021) demonstrated that students with AR have more productive academic trajectories consistently, report better grades, experience more satisfaction with their academic lives, and have lower dropout intentions due to better engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies linking EI and AP often cite AR as a contextual resource (Thomas & Zolkoski, 2020;Suleman et al, 2019), which suggests that AR relates with both EI and AP (Slåtten et al, 2021). Concerning the AR-AP link, Bittmann (2021) demonstrated that students with AR have more productive academic trajectories consistently, report better grades, experience more satisfaction with their academic lives, and have lower dropout intentions due to better engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, in-depth analysis is needed to deeply grasp the role of gender and age as different roles between emotional ability and resilience. Through combing the previous literature, studies on the emotional ability and resilience of young children have confirmed that they are related to age and gender, but they failed to identify the differences arising from the relationship between the two [ 50 , 51 , 55 , 56 ]. Zeeman et al (2017) confirmed that the performance of emotional ability and resilience in young groups are affected by gender and sexual orientation [ 57 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…EI has its roots in the concept of social intelligence and is considered as comprising intrapersonal and interpersonal intelligence of an individual (Law et al, 2004). The concept of EI has guided numerous investigations over the past 25 years; however, a large body of literature suggest that EI influences individuals' responses to stress and contributes to resilience when confronted with adverse life events (Thomas & Zolkoski, 2020). That is, emotionally intelligent individuals effectively adapt to a given situation by adopting appropriate coping and interpersonal skills by effectively controlling their emotions (Choi et al, 2018).…”
Section: Original Researchmentioning
confidence: 99%